Caracterização do amido do mangarito - Mendonça, Marcelle Mendes (2019)
The mangarito (Xanthosoma riedelianum) is a vegetable that was widely used in the past by the people of the Central American region. However, the plant is currently in the group of unconventional vegetables. However, some preliminary studies have shown that the cuff has starch as its main component, being considered eminently caloric. In view of the above, the objective of this study was to characterize the mangarito starch and evaluate its properties for the food industry. After extraction, the starch was characterized by its morphological, thermal and technological properties. Morphological characteristics were evaluated by granule size distribution, scanning electron microscopy and X-ray analyzes. The thermal properties were examined by determining the initial, peak and final temperatures of gelatinization and retrogradation; and related to the technological properties that were determined by the analysis of viscosity, swelling power, solubility, paste clarity, and syneresis. Density, pH and titratable acidity analyses were also performed. Results were analyzed with mean and standard deviation observations. Variance analysis was performed for swelling power, solubility, paste clarity and syneresis. The yield of the mangarito starch extraction process was 7.89 %, and it is low in moisture, with granules without surface porosity, circular, smooth, with some irregularities, particle size with the polymodal distribution. They present type B polymorphism, with a crystallinity index of 41.20 %, which is in agreement with the crystallinity index of native starches. The gelatinization temperature determined by the DSC is 67.63 °C while the paste temperature determined by the RVA is 77.9 °C, an expected difference due to the high sensitivity of the differential scanning calorimeter equipment. In the mangarito starch, three thermal events of mass loss are observed, presenting 96.86 % of mass accumulating loss and 3.14 % of ash. Cuff starch has high sticking temperature, high mechanical stirring resistance, high tendency to retrograde and high final viscosity. The swelling power of the granules shows continuous growth during the temperature increase, while the solubility index has a similar behavior up to 70 º C and then there is reduction insolubility. The clarity of the cuff starch paste decreases with storage time. The absolute density of the starch studied is 1.47 g cm -3 , the pH is close to neutrality and the titratable acidity within the range of starches from rhizomatous sources. Mango starch, therefore, is a good source for making puddings, pie fillings, baby foods, and bakery products because it has high viscosity and can be used in broth formulation. because it displayed an opaque folder.